5(e+1)=3(2e-1)

Simple and best practice solution for 5(e+1)=3(2e-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(e+1)=3(2e-1) equation:


Simplifying
5(e + 1) = 3(2e + -1)

Reorder the terms:
5(1 + e) = 3(2e + -1)
(1 * 5 + e * 5) = 3(2e + -1)
(5 + 5e) = 3(2e + -1)

Reorder the terms:
5 + 5e = 3(-1 + 2e)
5 + 5e = (-1 * 3 + 2e * 3)
5 + 5e = (-3 + 6e)

Solving
5 + 5e = -3 + 6e

Solving for variable 'e'.

Move all terms containing e to the left, all other terms to the right.

Add '-6e' to each side of the equation.
5 + 5e + -6e = -3 + 6e + -6e

Combine like terms: 5e + -6e = -1e
5 + -1e = -3 + 6e + -6e

Combine like terms: 6e + -6e = 0
5 + -1e = -3 + 0
5 + -1e = -3

Add '-5' to each side of the equation.
5 + -5 + -1e = -3 + -5

Combine like terms: 5 + -5 = 0
0 + -1e = -3 + -5
-1e = -3 + -5

Combine like terms: -3 + -5 = -8
-1e = -8

Divide each side by '-1'.
e = 8

Simplifying
e = 8

See similar equations:

| m^2+25m=0 | | 4(3x-2)+3(x+1)=100 | | 3p-4=10 | | 3x+2=42 | | x(x+2)=159+6(x+x+2) | | 8=3x^2-2x | | 8=3x*3x-2 | | X=3+0.25x | | X=3+0.25 | | 3Q=2P-M | | 2x-4u-5=0 | | (343)1/4(343)-1/12 | | 3(2p-7)=4p-5 | | f(-3)=-3 | | 8X+14=38+2x | | 8X+14=38+2 | | h^2-2h=0 | | 2x+3=10-3x | | 1/2X7 | | 10x-4=5x+15 | | 12-(-y-19)=12 | | 5z^2-4z^4-4=0 | | x=(5x-6)+21 | | 23X-5X^2=-24 | | 4.6=5.8-p | | -(-3-7g)-11=-9-5g | | 6x^2-73x-63=0 | | 3[x-3]+2=13-x | | 3a+7(5a+7b)-10(3+5b)=14ab+50(3+4) | | 2[3x+2(x-2)]+19=(3x+1)*2 | | 8x+3-(7+9x)=-8 | | 2(3c+2d)-2(5c-3d)= |

Equations solver categories